2011
DOI: 10.1103/physrevlett.107.118301
|View full text |Cite
|
Sign up to set email alerts
|

Overlimiting Current in a Microchannel

Abstract: We revisit the classical problem of diffusion-limited ion transport to a membrane (or electrode) by considering the effects of charged side walls. Using simple mathematical models and numerical simulations, we identify three basic mechanisms for over-limiting current in a microchannel: (i) surface conduction carried by excess counterions, which dominates for very thin channels, (ii) convection by electro-osmotic flow on the side walls, which dominates for thicker channels and transitions to (iii) electro-osmot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

33
409
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 246 publications
(444 citation statements)
references
References 32 publications
33
409
2
Order By: Relevance
“…In order to limit excessive grid refinement near membrane surfaces, the equations were solved with a dimensionless Debye length, λ = 10 −3 , far larger than a physically realistic value (i.e., ∼10 −4 ). Other studies [6,7,[15][16][17][18] employ similar dimensionless Debye length values, and as shown below, the simulation results are clearly qualitatively similar to the realistic phenomenon observed in the experiment.…”
Section: -2supporting
confidence: 78%
See 1 more Smart Citation
“…In order to limit excessive grid refinement near membrane surfaces, the equations were solved with a dimensionless Debye length, λ = 10 −3 , far larger than a physically realistic value (i.e., ∼10 −4 ). Other studies [6,7,[15][16][17][18] employ similar dimensionless Debye length values, and as shown below, the simulation results are clearly qualitatively similar to the realistic phenomenon observed in the experiment.…”
Section: -2supporting
confidence: 78%
“…In the overlimiting regime, wider channels sustain parallel helical vortices, a surprising result first observed in 3D simulation and then verified experimentally. The 3D simulation was performed using our customized Poisson-Nernst-Planck-Navier-Stokes solver, and the initial experiments were performed using our microscale electrical desalination system designed specifically for observing ion transport processes in detail [17]. Below we describe a comprehensive experimental and numerical characterization of a device exhibiting this recently discovered 3D electrokinetic instability.…”
Section: Introductionmentioning
confidence: 99%
“…The overlimiting conductance found in this model is approximately three times larger than the conductance found in Ref. [26], where diffusion and advection in the diffuse double layers is neglected. In the limit of negligible surface charge the numerical results agree with our previous analytical model [8] for the overlimiting current due to an extended spacecharge region.…”
Section: Introductioncontrasting
confidence: 58%
“…Sketch of a charged cylindrical pore subjected to water flow, electrical current, and salt flux between a high-salinity (left) and low-salinity (right) reservoir. and diffusion dominate, although nonequilibrium structures, such as "salt fingers" extending along the pore surfaces, can arise in microchannels, if electro-osmotic convection dominates [41,44,45,48]. Here, we neglect such effects and focus on deriving the consequences of local (but not global) quasiequilibrium.…”
Section: Introductionmentioning
confidence: 99%